Transcriptome responses to heat and cold stress in prepupae of Trichogramma chilonis. Issue 9 (11th March 2021) - Yi, Jiequn; Liu, Jianbai; Li, Dunsong; Sun, Donglei; Li, Jihu; An, Yuxing; Wu, Han
Abstract: Trichogramma is a useful species that is widely applied in biocontrol. Temperature profoundly affects the commercial application of T. chilonis . Different developmental transcriptomes of prepupae and pupae of T. chilonis under 10, 25, and 40°C were obtained from our previous study. In this study, transcriptomic analysis was further conducted to gain a clear understanding of the molecular changes in the prepupae of T. chilonis under different thermal conditions. A total of 37, 295 unigenes were identified from 3 libraries of prepupae of T. chilonis, 17, 293 of which were annotated. Differential expression analysis showed that 408 and 108 differentially expressed genes (DEGs) were identified after heat and cold treatment, respectively. Under heat stress, the pathway of protein processing in endoplasmic reticulum was found to be active. Most of the genes involved in this pathway were annotated as lethal (2) essential for life [ l(2)efl ] and heat shock protein genes ( hsps ), which were both highly upregulated. Nevertheless, most of the genes involved in another significantly enriched pathway of starch and sucrose metabolism were downregulated, including 1 alpha‐glucosidase gene and 2 beta‐glucuronidase genes. Under cold stress, no significantly enriched pathway was found, and the significantly enriched GO terms were related to the interaction with host and immune defenses. Together, these results provide us with a comprehensive view of the molecular mechanisms of T. chilonis in response to temperature stresses and will provide new insight into the mass rearing and utilization of T. chilonis . Abstract : Transcriptomic responses to thermal stresses were characterized in prepupal Trichogramma chilonis . Two pathways were significantly enriched after heat treatment which may be important for heat tolerance in T. chilonis . A few DEGs were significantly enriched into GO terms related to interactions with host and immune defenses after cold treatment.